Assessment of the sustainability in dehesa farms according to size and livestock prevalence - Gaspar Garcia, P; Mesias Diaz, F J; Escribano Sanchez, M; Pulido Garcia, F (ITEA-INFORMACION TECNICA ECONOMICA AGRARIA, 2009)
Assessment of the sustainability in dehesa farms according to size and livestock prevalence This paper presents an evaluation of the sustainability of the dehesa livestock systems located in Extremadura (SW Spain). We apply a methodological adaptation of the framework known as MESMIS (Framework for the Evaluation of Management Systems incorporating Sustainability Index). This method is based on the valuation of basic attributes of sustainability using indicators and indices that allow simultaneous and comparative analyses of farms based on their size and productive orientation. A global value of sustainability for each typology present in dehesa is obtained from a fundamentally technical-economic perspective, taking into account some environmental and social aspects. The dimension of the operation influences the capacity of adaptation of operations, with bigger farms showing better adaptability. The smaller farms compensate their management by improving productivity levels. We also observe that the presence of Iberian pig improves the sustainability index of the operations.
Keywords: Dehesa; extensive livestock; farm management; Sustainability indicators

Assessment of the sustainability in dehesa farms according to size and livestock prevalence - Gaspar García, P.; Mesias Diaz, F. J.; Escribano Sanchez, M.; Pulido Garcia, F. (ITEA-INFORMACION TECNICA ECONOMICA AGRARIA, 2009)
Assessment of the sustainability in dehesa farms according to size and livestock prevalence This paper presents an evaluation of the sustainability of the dehesa livestock systems located in Extremadura (SW Spain). We apply a methodological adaptation of the framework known as MESMIS (Framework for the Evaluation of Management Systems incorporating Sustainability Index). This method is based on the valuation of basic attributes of sustainability using indicators and indices that allow simultaneous and comparative analyses of farms based on their size and productive orientation. A global value of sustainability for each typology present in dehesa is obtained from a fundamentally technical-economic perspective, taking into account some environmental and social aspects. The dimension of the operation influences the capacity of adaptation of operations, with bigger farms showing better adaptability. The smaller farms compensate their management by improving productivity levels. We also observe that the presence of Iberian pig improves the sustainability index of the operations.
The following values have no corresponding Zotero field: pub-location: AVDA MONTANANA 930, APARTADO 727, ZARAGOZA, 50080, SPAIN publisher: ASOCIACION INTERPROFESIONAL DESARROLLO AGARIO
Keywords: Dehesa; extensive livestock; farm management; Sustainability indicators

Evaluación de la sostenibilidad en exploraciones de dehesa en función de su tamaño y orientación ganadera - Gaspar Garcia, P; Mesías Díaz, Francisco Javier; Escribano Sánchez, Miguel; Pulido, F (ITEA, información técnica económica agraria, 2009)
Keywords: dehsa; extensive livestock; farm management; Sustainability indicators

Evaluación de la sostenibilidad en exploraciones de dehesa en función de su tamaño y orientación ganadera - Gaspar García, P.; Mesías Díaz, Francisco Javier; Escribano Sánchez, Miguel; Pulido, F. (ITEA, información técnica económica agraria, 2009)
Keywords: dehsa; extensive livestock; farm management; Sustainability indicators

Sustainability in Spanish Extensive Farms (Dehesas): An Economic and Management Indicator-Based Evaluation - Gaspar, P; Mesías, F J; Escribano, M; Pulido, F (Rangeland Ecology & Management, 2009)
The dehesa is defined as an agroforestry system that is characteristic of the southwestern Iberian Peninsula, where grassland is combined with evergreen species of the genus Quercus. Those systems have been gradually transformed from the Mediterranean forest into a unique kind of pastoral woodland by means of an agricultural use. Dehesas occupy more than 6 million ha, and the livestock systems that are based in them are of vital importance for their sustainability. The present work classifies, describes, and evaluates the sustainability of these systems in the Spanish region of Extremadura (southwestern Spain). To this end, we apply a methodological adaptation of the Framework for the Evaluation of Management Systems incorporating Sustainability Index (MESMIS). MESMIS is based on the evaluation of basic attributes of sustainability from indicators that allow one to make a simultaneous and comparative analysis of different types of farms. For the study, 69 farms were selected at random, and were classified using multivariate techniques into four types according to their level of intensification and productive orientation. The results were used to obtain an overall value of sustainability from a technical economic perspective for each farm type present in the dehesa. The mixed systems (beef cattle–sheep–Iberian pigs) have been found to be the most sustainable in general terms. The high–stocking rate sheep dehesas are the least sustainable, although at present, they are the most profitable. The other two groups analyzed, “low–stocking rate sheep farms” and “beef cattle farms,” had intermediate and similar scores. Mixed livestock dehesa farms are the closest to the traditional systems with a highly diverse production, an optimal use of the system's resources, and little dependence on external subsidies. In the present context, with uncertainties about European Union subsidies, this type of farm should be a goal for dehesa farmers.
Keywords: livestock production; management strategies; MESMIS; Rangelands; Sustainability indicators

Sustainability in Spanish Extensive Farms (Dehesas): An Economic and Management Indicator-Based Evaluation - Gaspar, P.; Mesías, F. J.; Escribano, M.; Pulido, F. (Rangeland Ecology & Management, 2009)
The dehesa is defined as an agroforestry system that is characteristic of the southwestern Iberian Peninsula, where grassland is combined with evergreen species of the genus Quercus. Those systems have been gradually transformed from the Mediterranean forest into a unique kind of pastoral woodland by means of an agricultural use. Dehesas occupy more than 6 million ha, and the livestock systems that are based in them are of vital importance for their sustainability. The present work classifies, describes, and evaluates the sustainability of these systems in the Spanish region of Extremadura (southwestern Spain). To this end, we apply a methodological adaptation of the Framework for the Evaluation of Management Systems incorporating Sustainability Index (MESMIS). MESMIS is based on the evaluation of basic attributes of sustainability from indicators that allow one to make a simultaneous and comparative analysis of different types of farms. For the study, 69 farms were selected at random, and were classified using multivariate techniques into four types according to their level of intensification and productive orientation. The results were used to obtain an overall value of sustainability from a technical economic perspective for each farm type present in the dehesa. The mixed systems (beef cattle–sheep–Iberian pigs) have been found to be the most sustainable in general terms. The high–stocking rate sheep dehesas are the least sustainable, although at present, they are the most profitable. The other two groups analyzed, “low–stocking rate sheep farms” and “beef cattle farms,” had intermediate and similar scores. Mixed livestock dehesa farms are the closest to the traditional systems with a highly diverse production, an optimal use of the system's resources, and little dependence on external subsidies. In the present context, with uncertainties about European Union subsidies, this type of farm should be a goal for dehesa farmers.
Keywords: livestock production; management strategies; MESMIS; Rangelands; Sustainability indicators

An experts survey on sustainability across twenty-seven extensive European systems of grassland management. - Caballero, Rafael; Gil, Angel; Fernández-Santos, Xavier (Environmental management, 2008)
European Large Scale Grazing Systems (LSGS) are at a crossroad with environmental, agronomic, and social factors interacting on their future viability. This research assesses the current environmental and socio-economic status of a wide range of European LSGS according to an agreed subset of sustainability criteria and indicators, which have been recognized by corresponding experts and privileged observers on their respective case-study system. A survey questionnaire was drafted containing five main criteria (pastoral use, environmental, economic, social, and market and development), with four conceptual-scored variables (indicators) within each criterion. Descriptive, analytical and clustering statistical techniques helped to draw a synthesis of the main result and to standardize sustainability variables across different biogeographical regions and management situations. The results show large multicollinearity among the 20 variables proposed. This dependence was revealed by the reduction to six main factor-components, which accounted for about 73% of the total variance in responses. Aggregation of point-score indicators across criteria to obtain a sustainability index can be of less policy relevance than responses to specific criteria or indicators. Affinity between case-study systems, as judged by collaborative-expert responses, was not related to biogeographical location, operating livestock sector, or population density in their areas. The results show larger weaknesses and constraints in the economic and social criteria than in the pastoral and environmental criteria, and the large heterogeneity of responses appears in the social criterion.
Keywords: European agriculture; Low-input grazing systems; Sustainability indicators

An experts survey on sustainability across twenty-seven extensive European systems of grassland management. - Caballero, Rafael; Gil, Angel; Fernández-Santos, Xavier (Environmental management, 2008)
European Large Scale Grazing Systems (LSGS) are at a crossroad with environmental, agronomic, and social factors interacting on their future viability. This research assesses the current environmental and socio-economic status of a wide range of European LSGS according to an agreed subset of sustainability criteria and indicators, which have been recognized by corresponding experts and privileged observers on their respective case-study system. A survey questionnaire was drafted containing five main criteria (pastoral use, environmental, economic, social, and market and development), with four conceptual-scored variables (indicators) within each criterion. Descriptive, analytical and clustering statistical techniques helped to draw a synthesis of the main result and to standardize sustainability variables across different biogeographical regions and management situations. The results show large multicollinearity among the 20 variables proposed. This dependence was revealed by the reduction to six main factor-components, which accounted for about 73% of the total variance in responses. Aggregation of point-score indicators across criteria to obtain a sustainability index can be of less policy relevance than responses to specific criteria or indicators. Affinity between case-study systems, as judged by collaborative-expert responses, was not related to biogeographical location, operating livestock sector, or population density in their areas. The results show larger weaknesses and constraints in the economic and social criteria than in the pastoral and environmental criteria, and the large heterogeneity of responses appears in the social criterion.
The following values have no corresponding Zotero field: accession-num: 18491183
Keywords: European agriculture; Low-input grazing systems; Sustainability indicators